KUALITAS PELAYANAN PERPUSTAKAAN PADA SEKOLAH MENENGAH KEJURUAN NEGERI 1 SEYEGAN SLEMAN - Fitrawan, Refanda Januar; Yunanto, Mohammad Kus (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
The quality of library services is important, especially in schools, according to a study. In order to create quality graduate profiles, libraries that assist student learning play a crucial role. Since it is one of the biggest SMKNs in the West Sleman region, this research is being conducted at SMKN 1 Seyegan. This study aims to evaluate and assess the quality of the school library at SMKN 1 Seyegan Sleman. This study used a descriptive, qualitative approach to its research methodology. Observation, interviews, and documentation were used as data-gathering methods. Purposive and snowball sampling were the methods used to identify the informants. Techniques for collecting data, reducing it, presenting it, and deriving conclusions are all used in data analysis. The results of this research indicate that: (1) Reliability indicators have been put into practice and are generally strong, but certain of its sub-indicators namely, accuracy in student service delivery have not performed as predicted; (2) Although service delivery is not on time, quality indicators are fairly good; (3) The indicator of empathy has been implemented well, but other of its components namely, giving students' interests priority have not performed as intended; (4) While responsiveness indicators have been executed quite well, some sub-indicators have fallen short of expectations, including the provision of prompt and accurate services given that there is only one librarian; (5) While the tangible indicators have been put into place and are doing well, there are several sub-indicators that still require improvement, particularly the quality of the library facilities.Keyword: service; quality; library.